Wort und Unwort des Jahres. Sprache als Spiegelbild gesellschaftspolitischer Prozesse - Peter Chmiel (Studia Linguistica)
The Society for the German Language (GfdS) in Wiesbaden has been selecting the word of the year since 1971. The first “winner” in the surveys was the adjective aufmüpfig (‘rebellious’), followed in second and third place by the nouns Junktim and Umweltschutz (‘environmental protection’). 20 years later, the ‘non-word’ of the year was added to the list. The list of non-words was opened in 1991 by the adjective ausländerfrei (‘free of foreigners’). The announcement of the selected terms has since become a public event with far-reaching resonance and sometimes controversial discussions (keyword: ‘semantic battles’). In this article, the author places the topic in the context of linguistic research and describes the socio-economic and day-to-day political background that largely determines the respective selection of words and non-words. Several examples are used to focus on the influence of socio-political circumstances on the use of language (such as the fall of the Berlin Wall and reunification, migration and xenophobia, Russia’s war against Ukraine as a turning point).